GESTATIONAL DIABETES MELLITUS - Bektemirova Zukhra (Modern American Journals, 2025)
Gestational diabetes mellitus (GDM) is a common metabolic disorder characterized by glucose intolerance with onset or first recognition during pregnancy. It arises primarily due to pregnancy-induced insulin resistance mediated by placental hormones, combined with inadequate pancreatic β-cell compensation. The prevalence of GDM has increased globally, reflecting rising maternal age, obesity, and sedentary lifestyles. Although often asymptomatic, GDM is associated with significant short- and long-term complications for both mother and offspring, including preeclampsia, cesarean delivery, fetal macrosomia, neonatal hypoglycemia, and an increased lifetime risk of type 2 diabetes mellitus. Diagnosis is typically established through oral glucose tolerance testing during the second trimester, while management focuses on medical nutrition therapy, physical activity, glucose monitoring, and pharmacological treatment when necessary, with insulin as the preferred therapy. Postpartum follow-up is essential due to the high risk of recurrent glucose intolerance and future metabolic disease. Early detection and appropriate management of GDM are crucial to improving maternal and neonatal outcomes and reducing long-term health risks.
Keywords: Gestational diabetes mellitus; pregnancy; insulin resistance; hyperglycemia; maternal outcomes; neonatal outcomes; glucose tolerance test; metabolic disorders